2015
DOI: 10.1016/j.virol.2015.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus (VZV) origin of DNA replication oriS influences origin-dependent DNA replication and flanking gene transcription

Abstract: The VZV genome has two origins of DNA replication (oriS), each of which consists of an AT-rich sequence and three origin binding protein (OBP) sites called Box A, C and B. In these experiments, the mutation in the core sequence CGC of the Box A and C not only inhibited DNA replication but also inhibited both ORF62 and ORF63 expression in reporter gene assays. In contrast the Box B mutation did not influence DNA replication or flanking gene transcription. These results suggest that efficient DNA replication enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
4
0
3
Order By: Relevance
“…Whole cell lysates of VZV infected and uninfected melanoma cells were prepared in lysis buffer (50 mM Tris-HCl, pH 7.5, 0.15 M NaCl, 1 mM EDTA, 0.1% Triton X-100 and protease inhibitor cocktail (Roche, Mannheim, GE, added per the manufacturer’s instructions) and analyzed for IE62 and IE63 expression by immunoblot as previously described (Khalil et al, 2015a). Antibodies against full length IE62 and IE63 were used as described previously (Spengler et al, 2000; and Zuranski et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell lysates of VZV infected and uninfected melanoma cells were prepared in lysis buffer (50 mM Tris-HCl, pH 7.5, 0.15 M NaCl, 1 mM EDTA, 0.1% Triton X-100 and protease inhibitor cocktail (Roche, Mannheim, GE, added per the manufacturer’s instructions) and analyzed for IE62 and IE63 expression by immunoblot as previously described (Khalil et al, 2015a). Antibodies against full length IE62 and IE63 were used as described previously (Spengler et al, 2000; and Zuranski et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…O vírus varicela-zoster (VZV) é um herpesvirus neurotrópico, que causa uma infecção primária denominada varicela, e a inflamação secundária designa-se de herpes zoster, que ocorre pela reativação do vírus da fase de latência presente nos neurônios do nervo craniano, raiz dorsal e gânglios sensoriais 27,31,59,60,61 . O VZV é a segunda causa mais comum de encefalite viral, e acomete crianças, que apresentam manifestação comum como ataxia cerebelar e/ou encefalite difusa; e em pacientes idosos ou imunocomprometidos ocorre a reativação viral 27,31,59,60,61,62 .…”
Section: Vírus Varicella-zoster (Vzv)unclassified
“…A encefalite por VZV é reconhecida pelo termo vasculopatia cerebral, pois se caracteriza por uma inflamação nos vasos endoteliais cerebrovasculares causando déficit neurológico focal agudo após a distribuição trigeminal por semanas a meses, e/ou infecção de células coróides 27,32,62 . Essa infecção ocorre com maior frequência no SNC e causa cerebelite, predominando em crianças com varicela 27,31,59,62 . A encefalite associada ao herpes zoster pode manifestar um quadro de vasculite 27,31,59,62 .…”
Section: Vírus Varicella-zoster (Vzv)unclassified
See 1 more Smart Citation
“…VZV genome contains OriS, and probably lacks the replication origin at the UL segmentalthough Khalil et al showed that OriS mutations do not completely impede VZV replication in cell culture, suggesting an alternative, hidden OriL 293 . We identified nine nroRNAs starting in the proximity of VZV OriS.…”
Section: Near-replication-origin (Nro)rnasa Novel Class Of Transcriptsmentioning
confidence: 99%